The Area-Based Development of Phra Bundit Asa and Phra Dhammacarika for Solutions of Poverty of the Highland People - Phrakhru Piladdhammakorn (Natthaphon Prachunha); Phrakhru Pisutchayanusask (Chitchai Seedokmai); Tasonthi, Somboon; Talanuk, Decha; Junpundao, Buaswan (Dhammathas Academic Journal, 2024)
The aims of this research encompass several key objectives: 1) Investigate the contextual factors, prevailing conditions, challenges, barriers, and requirements essential for the progress of highland regions. 2) Examine the roles, responsibilities, mandates, and operational parameters of Phra Bundit Asa and Phra Dhammacarika in highland areas. 3) Explore the fundamental principles of community development in highland regions and devise innovative community solutions rooted in Buddhist principles to address poverty among highland inhabitants. 4) Propose a spatial development model integrating Buddhist innovations from Phra Bandit Asa and Phra Dhammacarika tailored for highland contexts. This research employs a blend of qualitative methods and participatory action research across three community research sites: Ban Dok Daeng, Ban Huai Bong, and Ban Chan, engaging with a cohort of 25 key informants. Methodological tools include spatial surveys, in-depth interview protocols, and before-after activity assessments, with data analyzed and findings summarized descriptively. The research findings reveal the following insights: 1. Context: The highland populace exhibits a diverse social landscape encompassing factors such as ethnicity, religion, education, debt, income, and occupation. Despite this diversity, the issue of poverty persists without tangible resolution. Insufficient income to cover expenses and mounting debts compound their challenges. Geographical constraints, resource scarcity, and limited access to services and information exacerbate their predicament. Addressing these challenges necessitates a focus on local economic promotion and the development of agriculture and industries suited to the environment. 2. Roles, duties, missions, and performance conditions of Phra Budit Asa and Phra Dhammacarika involve various facets: 1) Propagation of Buddhism. 2) Cultivation of mental well-being. 3) Preservation of arts and culture. 4) Advocacy for watershed forest conservation. 5) Dissemination of knowledge on the dangers of drug abuse. 3. Principles of highland community development and community innovation, rooted in Buddhist principles such as tiṭṭhadhammikattha or virtues conducive tobenefits in the present, emphasize: - Fostering a millionaire's mindset to address poverty. - Prioritizing self-reliance. - Advocating for the conservation of natural resources. - Leveraging temples as hubs for local wisdom dissemination. - Encouraging community involvement and participation. 4. Proposed model for spatial development integrating Buddhist innovations includes: 1) Empowering self-reliance among communities. 2) Advocating for the conservation of natural resources. 3) Leveraging temples as educational centers for local wisdom. 4) Facilitating active community participation in development initiatives.